Pre-Service Teachers’ MPCK Enhancements Using the Framework of Anthropological Theory of the Didactic - Lopez-Conde, Rosie (Archīum Ateneo, 2021)
This study aims to provide an intervention to the teacher education programs of the Philippines in response to the dismal results in TEDS-M 2008. The intervention here developed is a prototype that focuses on teaching Instrumentation in Mathematics within the anthropological theory of the didactic (ATD) by using the notions of the study and research paths (RSP) and praxeologies. The intervention is developed in the Didactics of Mathematics Course (DMC). Moreover, the DMC prototype is tested to be then replicated to help to improve the Mathematics Pedagogical Content Knowledge (MPCK) of pre-service teachers. It could also take part in the pre-service teacher education curriculum as a new course for future mathematics teachers. This intervention addressed the need to develop MPCK. We conclude that the DMC Prototype is practical and effective. Results showed that DMC enhanced the pre-service teachers’ MPCK (Z = −2.96, p = 0.003).